Educational Institutions and Muslim Harmony: Ahl al-Sunnah wal-Jama‘ah View (Contrarius Series: Law & Social Justice, 2026)
This study explored how educational institutions can help sustain harmony amongst the Muslim community according to the Ahl al-Sunnah wal-Jama‘ah (ASWJ) perspective. Formal and informal educational institutions serve as the main agents that shape the faith (ʿaqīdah), thought and character of the Muslim generation, while ensuring that Islamic values grounded in the ASWJ framework continue to be inherited, practiced and strengthened amongst the community. This qualitative study employed document analysis, library research, classical texts and contemporary literary works that emphasize the ʿaqīdah concept and its relationship with ASWJ theology. Findings indicate that educational institutions function as the primary medium for strengthening ʿaqīdah and building a harmonious society based on the ASWJ manhaj (doctrine), as well as serving as a platform for the inculcation of Wasatiyyah (moderation) and tolerance values that are fundamental to social harmony. Educational institutions also act as an effective defence mechanism against the influence of deviant ideologies and doctrines that could threaten the stability and unity of the Muslim community. It can be concluded that educational institutions grounded in the ASWJ doctrine play a crucial role in sustaining a harmonious Muslim society by strengthening doctrinal coherence, promoting social stability, and contributing to the long-term development of cohesive and resilient Muslim communities.